Development of novel real-time PCR methodology for quantification of COL11A1 mRNA variants and evaluation in breast cancer tissue specimens - Karaglani,M.; Toumpoulis,I.; Goutas, N.; Poumpouridou,N.; Vlachodimitropoulos, D.; Vasilaros,S.; Rizos, I; Kroupis, C. (BMC.Cancer, 2015)
BACKGROUND: Collagen XI is a key structural component of the extracellular matrix and consists of three alpha chains. One of these chains, the alpha1 (XI), is encoded by the COL11A1 gene and is transcribed to four different variants at least (A, B, C and E) that differ in the propensity to N-terminal domain proteolysis and potentially in the way the extracellular matrix is arranged. This could affect the ability of tumor cells to invade the remodeled stroma and metastasize. No study in the literature has so far investigated the expression of these four variants in breast cancer nor does a method for their accurate quantitative detection exist. METHODS: We developed a conventional PCR for the general detection of the general COL11A1 transcript and real-time qPCR methodologies with dual hybridization probes in the LightCycler platform for the quantitative determination of the variants. Data from 90 breast cancer tissues with known histopathological features were collected. RESULTS: The general COL11A1 transcript was detected in all samples. The developed methodologies for each variant were rapid as well as reproducible, sensitive and specific. Variant A was detected in 30 samples (33 %) and variant E in 62 samples (69 %). Variants B and C were not detected at all. A statistically significant correlation was observed between the presence of variant E and lymph nodes involvement (p = 0.037) and metastasis (p = 0.041). CONCLUSIONS: With the newly developed tools, the possibility of inclusion of COL11A1 variants as prognostic biomarkers in emerging multiparameter technologies examining tissue RNA expression should be further explored
Keywords: Adult; Aged; Alternative Splicing; Biomarkers,Tumor; Breast Neoplasms; Collagen Type XI; Diagnosis; Female; gene expression; Genetic Variation; genetics; Humans; Kaplan-Meier Estimate; Middle Aged; mortality; Neoplasm Grading; Neoplasm Metastasis; Neoplasm Staging; Real-Time Polymerase Chain Reaction; RNA,Messenger; Tumor Burden